Association of glucocerebrosidase polymorphisms and mutations with dementia in incident Parkinson's disease. Issue 10 (21st May 2018) - Lunde, Kristin Aaser; Chung, Janete; Dalen, Ingvild; Pedersen, Kenn Freddy; Linder, Jan; Domellöf, Magdalena E.; Elgh, Eva; Macleod, Angus D.; Tzoulis, Charalampos; Larsen, Jan Petter; Tysnes, Ole‐Bjørn; Forsgren, Lars; et al.
Abstract: Introduction: Both polymorphisms and mutations in glucocerebrosidase ( GBA ) may influence the development of dementia in patients with Parkinson's disease. Methods: Four hundred forty‐two patients and 419 controls were followed for 7 years. Dementia was diagnosed using established criteria. Participants were analyzed for GBA genetic variants, including E326K, T369M, and L444P. Associations between GBA carrier status and dementia were assessed with Cox survival analysis. Results: A total of 12.0% of patients with Parkinson's disease carried a GBA variant, and nearly half (22/53) of them progressed to dementia during follow‐up. Carriers of deleterious GBA mutations (adjusted hazard ratio 3.81, 95% confidence interval 1.35 to 10.72; P  = .011) or polymorphisms (adjusted hazard ratio 1.79; 95% confidence interval 1.07 to 3.00; P  = .028) progressed to dementia more rapidly than noncarriers. Discussion: GBA variants are of great clinical relevance for the development of dementia in Parkinson's disease, especially due to the relatively higher frequency of these alleles compared with other risk alleles.